Efektifitas Perangkap Feromon Kombinasi Warna Kuning Pada Tanaman Cabai Merah Keriting (Capsicum annum L.) - Firdaus, Ruly; Pramudi, Muhammad Indar; Marsuni, Yusriadi (www.ulm.ac.id, 2025)
The use of synthetic pesticides causes negative effects so research turns to natural control, one of which is the yellow trap. Yellow traps combined with the active ingredient methyl eugenol can reduce pesticide use by up to 75-95%. This study aims to evaluate the effectiveness of yellow combination pheromone traps on curly red chili plants (Capsicum annum L.). The method used was a Completely Randomized Design (CRD) with 24 traps and 3 treatments repeated 6 times. The results showed that trap installation was effective, with treatment T3 recording the highest insect intensity at 21.0% and T1 the lowest at 13.8%.